Pengembangan Desa Wangen sebagai Kawasan Wisata Islami - Ashidiqi, Hanif; , Dr. Ir. Qomarun, MM; , Nur Rahmawati S,ST,MT (2016)
Development of tourism is becoming a new industry that can affect various sectors further civilization. Indonesia although secular state but not entirely on the system that are still influenced by Islam . The existence of conventional tourism is synonymous with pleasure body fulfilling the needs and culture of consumption does not represent Islamic culture especially Indonesia where the majority is Muslim . Islamic tourism priority destinations usefulness not traveled to the place of Islam , but look for the usefulness and significance of the existence of these destinations.